2023
DOI: 10.3389/fnut.2023.1257439
|View full text |Cite
|
Sign up to set email alerts
|

Application of natural and modified additives in yogurt formulation: types, production, and rheological and nutraceutical benefits

Abigael Odunayo Bankole,
Emmanuel Anyachukwu Irondi,
Wasiu Awoyale
et al.

Abstract: Yogurt, a popular fermented dairy product, is of different types and known for its nutritional and nutraceutical benefits. However, incorporating additives into yogurt has been adopted to improve its functionality and nutraceutical properties. Additives incorporated in yogurt may be natural or modified. The incorporation of diverse natural additives in yogurt formulation, such as moringa, date palm, grape seeds and argel leaf extracts, cornelian cherry paste, mulberry fruit and leaf powder, lentil flour, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…Advocated by [1], [2], [32]- [34], food additives are classified into eight categories: Preservatives, Antioxidants, Emulsifiers and stabilizers¸ Colors/Coloring foodstuffs, Sweeteners, Flavor enhancers, Flavorings, and other additives at which preservatives according to [32], [35], [36] are utilized to keep some items safe over a period of time while extending their shelf life by preventing bacterial breakdown, which can result in toxin formation and food poisoning. Antioxidants, however, are antioxidants that delay oxidative degradation and increase the shelf life of food.…”
Section: Food Additivesmentioning
confidence: 99%
“…Advocated by [1], [2], [32]- [34], food additives are classified into eight categories: Preservatives, Antioxidants, Emulsifiers and stabilizers¸ Colors/Coloring foodstuffs, Sweeteners, Flavor enhancers, Flavorings, and other additives at which preservatives according to [32], [35], [36] are utilized to keep some items safe over a period of time while extending their shelf life by preventing bacterial breakdown, which can result in toxin formation and food poisoning. Antioxidants, however, are antioxidants that delay oxidative degradation and increase the shelf life of food.…”
Section: Food Additivesmentioning
confidence: 99%
“…Yoghurt can be the basis for the formulation of many types of dairy desserts by incorporating various categories of substances such as stabilizers, colorants, flavourants, sweeteners, or natural additives of plant origin [28]. Most of them are "yoghurts" with fruit, vegetables, cereals, nuts, seeds, plant/herbal extracts, byproducts, or even waste from fruit or vegetable processing [29,30].…”
Section: Emerging Technologies In the Dairy Sector: Some Research Exa...mentioning
confidence: 99%
“…Fermented food products have long been considered nutritious and health-promoting, with the potential to enhance nutrient availability ( 1 , 2 ). Yoghurt is a product of milk fermentation with a mixed or pure culture of lactic acid bacteria ( 3 , 4 ). The most common among the bacteria for yoghurt production are Streptococcus thermophilus and Lactobacillus bulgaricus , which generate bioactive peptides capable of enhancing human well-being and mitigating the risk of diseases ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have even suggested that synthetic additives may increase consumers’ susceptibility to certain diseases, such as diabetes and cancer, and may cause adverse reactions in the gastrointestinal, respiratory, dermatological, and neurological systems ( 22 , 24 ). These limitations of the synthetic additives, coupled with consumers’ growing demand for healthier food options, have prompted the exploration of natural additives in yoghurt formulation by previous researchers ( 4 ). In this context, Wajs et al ( 6 ) suggested that yoghurts enriched with natural additives are more valuable, particularly with respect to health-promoting constituents’ content, such as phenolic compounds, fibre, essential vitamins, minerals, and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation